Needs of patients with early psychosis: A comparison of patient’s and mental health care provider’s perception - AshaRani, P. V.; Tan, Yeow Wee Brian; Samari, Ellaisha; Wang, Peizhi; Cetty, Laxman; Satghare, Pratika; Ho, Jayne; Koh, Shiyun Astelle; Zhong Yi, Lee; Tang, Charmaine; Verma, Swapna; Subramaniam, Mythily (Frontiers in Psychiatry, 2022)
Background Needs define the capacity of a patient to benefit from health care services and a systematic assessment of needs allows planning and delivery of effective treatment to suit patients. This study aimed to understand the (a) needs felt by patients and those perceived by the care providers (CPs), (b) agreement between patients and CPs in the identified needs and (c) factors associated with unmet needs. Methods Participants (N = 215) were recruited through convenience sampling from the Early Psychosis Intervention Programme (EPIP). Data was captured from patients and CPs using the Camberwell Assessment of Needs Short Appraisal Schedule (CANSAS). Results Patients and CPs identified an average of 4.06 and 3.84 needs, respectively. The highest number of unmet needs were identified for the social (50% of patients and CPs) and health domains (31.13% of patients’ vs. 28.30% of CPs). Company, intimate relationships, psychotic symptoms, money, sexual expression and psychological distress, information and benefits were the unmet needs identified by patients, whereas company, intimate relationships, physical health, and daytime activities were identified by CPs. The concordance between patients and CPs was low with majority of the items scoring slight to fair agreement (Cohen’s kappa = 0–0.4). Older age, depression, severe anxiety and having Obsessive-Compulsive Disorder (OCD) were positively associated with unmet needs in patients. Conclusion While there was an overall consensus on the total needs and met needs between patients and CPs, the level of agreement between the two groups on various items were low. Different perceptions regarding unmet needs were noted between the groups. A holistic approach that takes into account different facets of the needs of patients together with strategic planning to address unmet needs might improve treatment outcomes and satisfaction.